2018
DOI: 10.33440/j.ijpaa.20200303.79
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cotton height spatial variability based on UAV-LiDAR

Abstract: The spatial variance of geometric information of farmland crops is the basis of field management. Therefore, it has significance for variable mechanical operations to accurately obtain the spatial difference of crop height information. In the present study, UAV-LiDAR was used to collect data at the cotton planting base in Korla to estimate the spatial differences in cotton plant height. The crop height was estimated using the average height of a certain number of highest points per m 2 point cloud. First, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Though more expensive than image-based 3D reconstructions such as structure-from-motion (SFM) [19][20][21], LiDAR systems have provided more accurate measurements of plant phenotypes such as height and biomass as a result of their finer spatial resolution compared to SFM [22]. LiDAR systems were utilized to estimate structural traits including height [21,23,24], leaf area index [25][26][27], biomass [19,20] and biotic or abiotic stresses that are expressed mostly via a change in the structural traits [15,[28][29][30]. LiDAR-based high-throughput phenotyping systems have been deployed for situations where the stress is expressed via the change in canopy color and have primarily been limited to applications in controlled environments.…”
Section: Introductionmentioning
confidence: 99%
“…Though more expensive than image-based 3D reconstructions such as structure-from-motion (SFM) [19][20][21], LiDAR systems have provided more accurate measurements of plant phenotypes such as height and biomass as a result of their finer spatial resolution compared to SFM [22]. LiDAR systems were utilized to estimate structural traits including height [21,23,24], leaf area index [25][26][27], biomass [19,20] and biotic or abiotic stresses that are expressed mostly via a change in the structural traits [15,[28][29][30]. LiDAR-based high-throughput phenotyping systems have been deployed for situations where the stress is expressed via the change in canopy color and have primarily been limited to applications in controlled environments.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that crop-specific CHM perform better than generalized crop models [11]. Studies were focused on segmentation of individual plants as is typical for maize [12,13] or on segmentation of entire field-trial plots in case of other cereals, sorghum or cotton [14][15][16][17]. The conversion of point-clouds to CHM can be done manually using software for digital terrain model processing [16], but specialized algorithms have also been reported [18].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple examples of accurate plant height estimates using UAV imagery have been shown in crops such as barley ( Hordeum vulgare L.) (Bendig et al ., 2014; Herzig et al ., 2021), cabbage ( Brassica oleracea var. capitata L.) (Moeckel et al ., 2018), cotton ( Gossypium hirsutum L.) (Feng et al ., 2019; Liu et al ., 2020), eggplant ( Solanum melongena L.) (Moeckel et al ., 2018), faba bean ( Vicia faba L.) (Ji et al ., 2022), maize (Anthony et al ., 2014; Geipel et al ., 2014; Grenzdörffer, 2014; Su et al ., 2019; Varela et al ., 2017; Anderson et al ., 2019; Malambo et al ., 2018; Shi et al ., 2016; Tirado et al ., 2020; Adak, Murray, Božinović, et al ., 2021; Letsoin et al ., 2023), potato ( Solanum tuberosum L.) (de Jesus Colwell et al ., 2021; Xie et al ., 2022; Njane et al ., 2023), rapeseed ( Brassica napus L.) (Xie et al ., 2021), sorghum ( Sorghum bicolor L.) (Chang et al ., 2017; Shi et al ., 2016; Watanabe et al ., 2017; Gano et al ., 2021), soybean ( Glycine max L.) (Li et al ., 2022), tomato ( Solanum lycopersicum L.) (Moeckel et al ., 2018), and wheat ( Triticum aestivum L.) (Holman et al ., 2016; Madec et al ., 2017; Michalski et al ., 2018; Volpato et al ., 2021). Studies on plant height using UAVs have shown variable levels of success when compared to manual measurements due to plant structure, field layout, and improvements in best practices as more research was completed (Holman et al ., 2016; Sweet et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%